Meningkatkan Hasil Belajar PAK Melalui Media Canva dalam Problem Based Learning Kelas IX SMP Negeri 1 Wonosari - Fisilia Ari Kuswanti; Anselmus Joko Prayitno; Roida Sihombing (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
There are still students of SMP Negeri 1 Wonosari, who have not fulfilled the expectations of the school's vision and mission which is to create people who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. This is evident in the fact that there are still students whose learning outcomes are low. To improve PAK learning outcomes, we tried using canva media in Problem Based Learning. To answer this problem, the researcher used an experimental method with 2 cycles using test and observation instruments. With research using qualitative descriptive data analysis methods. Based on the data obtained, the percentage of student learning outcomes in cycle I is 22% decent, 56% proficient and 22% advanced, which shows that there are still 2 children who need remedial. In cycle II, with canva media, learning outcomes increased to 0% feasible, 11% proficient and 89% advanced. This shows Problem Based Learning can improve critical thinking and learning outcomes.